Chemical Synthesis of Substituted Naphthalene Derivatives: A Review - Maheshwari, Mittali; Hussain, Nazar (Synthesis, 2023)
This review outlines progress in the synthesis of substituted naphthalene derivatives. Naphthalene and its derivatives exhibit various biological activities such as anti-inflammatory, anticancer, antiviral, antitubercular, antimicrobial, antihypertensive, antidiabetic, etc. Several strategies have been developed for the construction of naphthalene derivatives, primarily focused on metal-catalyzed reactions (palladium, copper, zinc, rhodium, platinum, nickel, etc.,) and Lewis acid catalyzed transformations. This review discusses the preparations of naphthalene derivatives using various salts such as gallium chlorides, gold chlorides, gold bromides, various gold complexes as well as Brønsted acids like triflic acid and trifluoroacetic acid, and Lewis acids such as boron trifluoride etherate. Additionally, miscellaneous types of reactions are explored involving both metal and Lewis acids. The transformational approaches covered in this review include cycloadditions, carboannulations, benzannulations, electroannulations, rearrangements, and cross-dehydrogenative coupling reactions. Overall this review provides a comprehensive and up-to-date account of the current state of preparations of substituted naphthalenes, highlighting their medicinal and industrial importance.1 Introduction1.1 Medicinal Importance of Naphthalenes2 Synthesis of Substituted Naphthalenes2.1 Metal-Catalyzed Reactions2.1.1 Palladium-Catalyzed Reactions2.1.2 Copper-Catalyzed Reactions2.1.3 Zinc-Catalyzed Reactions2.1.4 Iron-Catalyzed Reactions2.1.5 Rhodium-Catalyzed Reactions2.1.6 Platinum-Catalyzed Reactions2.1.7 Nickel-Catalyzed Reactions2.1.8 Other Metal-Catalyzed Reactions3 Lewis Acid Catalyzed Reactions4 Miscellaneous Reactions5 Conclusion
Keywords: naphthalene; metal catalysis; Lewis acid; Brønsted acid; annulation